Ultrastructural characteristics and immune profile of equine MSCs from fetal adnexa. Issue 4 (October 2017) - Iacono, Eleonora; Pascucci, Luisa; Rossi, Barbara; Bazzucchi, Cinzia; Lanci, Aliai; Ceccoli, Monica; Merlo, Barbara
Abstract : Both in human and equine species, mesenchymal stem cells (MSCs) from amniotic membrane (AM) and Wharton's jelly (WJ), may be particularly useful for immediate use or in later stages of life, after cryopreservation in cell bank. The aim of this study was to compare equine AM- and WJ-MSCs in vitro features that may be relevant for their clinical employment. MSCs were more easily isolated from WJ, even if MSCs derived from AM exhibited more rapid proliferation ( P  < 0.05). Osteogenic and chondrogenic differentiation were more prominent in MSCs derived from WJ. This is also suggested by the lower adhesion of AM cells, demonstrated by the greater volume of spheroids after hanging drop culture ( P  < 0.05). Data obtained by PCR confirmed the immunosuppressive function of AM and WJ-MSCs and the presence of active genes specific for anti-inflammatory and angiogenic factors (IL-6, IL 8, IL-β1). For the first time, by means of transmission electron microscopy (TEM), we ascertained that equine WJ-MSCs constitutively contain a very impressive number of large vesicular structures, scattered throughout the cytoplasm. Moreover, an abundant extracellular fibrillar matrix was located in the intercellular spaces among WJ-MSCs. Data recorded in this study reveal that MSCs from different fetal tissues have different characteristics that may drive their therapeutic use. These finding could be noteworthy for horses as well as for other mammalian species, including humans.